Light-induced charge density wave in LaTe3 - Kogar, Anshul; Zong, Alfred; Dolgirev, Pavel E.; Shen, Xiaozhe; Straquadine, Joshua; Bie, Ya-Qing; Wang, Xirui; Rohwer, Timm; Tung, I-Cheng; Yang, Yafang; Li, Renkai; Yang, Jie; et al. (Nature physics, 2020)
When electrons in a solid are excited by light, they can alter the free energy landscape and access phases of matter that are out of reach in thermal equilibrium. This accessibility becomes important in the presence of phase competition, when one state of matter is preferred over another by only a small energy scale that, in principle, is surmountable by the excitation. Here, we study a layered compound, LaTe 3 , where a small lattice anisotropy in the a – c plane results in a unidirectional charge density wave (CDW) along the c axis 1 , 2 . Using ultrafast electron diffraction, we find that, after photoexcitation, the CDW along the c axis is weakened and a different competing CDW along the a axis subsequently emerges. The timescales characterizing the relaxation of this new CDW and the reestablishment of the original CDW are nearly identical, which points towards a strong competition between the two orders. The new density wave represents a transient non-equilibrium phase of matter with no equilibrium counterpart, and this study thus provides a framework for discovering similar states of matter that are ‘trapped’ under equilibrium conditions. Short pulses of light shift the balance between two competing charge density wave phases, allowing the weaker one to manifest transiently while suppressing the stronger one. This shows that competing phases can be tuned in a non-equilibrium setting.